2014
DOI: 10.1051/limn/2014022
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of C and N isotopic signature of zooplankton: a seasonal study on a man-made lake in the Mediterranean region

Abstract: -Reservoirs are subject to severe fluctuations in the water level from seasonal and interannual climatic variations, as well as abstraction for irrigation, hydropower, and drinking water. This can affect the matter and energy transfer through the food web, of which zooplankton is of crucial importance. We traced seasonal changes in the carbon and nitrogen stable isotope signatures of suspended particulate matter and crustacean zooplankton from a small Mediterranean reservoir. The d 15 N SPM isotopic signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Hydrology, SPM and isotopic ratios SC was strongly affected by WLFs throughout the year (Fadda et al, 2014), with a clear seasonality as is generally reported for reservoirs in the Mediterranean area (Naselli-Flores, 2003;Geraldes and Boavida, 2005; Naselli-Flores and Barone, 2005). The lowest water level was reached in the autumn months (October and December) at the end of the driest period, and because of the constant year-round water withdrawal (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Hydrology, SPM and isotopic ratios SC was strongly affected by WLFs throughout the year (Fadda et al, 2014), with a clear seasonality as is generally reported for reservoirs in the Mediterranean area (Naselli-Flores, 2003;Geraldes and Boavida, 2005; Naselli-Flores and Barone, 2005). The lowest water level was reached in the autumn months (October and December) at the end of the driest period, and because of the constant year-round water withdrawal (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…∆ 15 N enrichment confirms some traits found in other lakes, independently from their size, typology, and trophy. In particular, cyclopoids were the most enriched in all but Lake Endine, in which the diaptomids were more enriched than the cyclopoids [20]. The small seasonal variability of δ 15 N signature also suggests a small plasticity in trophic position in all lakes but Pusiano, the hypereutrophic lake.…”
Section: Discussionmentioning
confidence: 91%
“…Carbon fractionation with respect to seston is therefore negligible, and seasonal changes in Daphnia carbon signature entirely overlap those of phytoplankton, thus providing a reliable pelagic baseline [6,8,[33][34][35]. Changes in carbon baseline signature with thermal stratification in turn reflect changes in taxa composition and carbon dynamics of phytoplankton in the upper water layers [6,20,21]. According to this interpretation, also in lakes Pusiano and Moro, summer thermal stratification led to increased contribution of the upper layers to phytoplankton production in summer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, seasonality was also observed in isotopic carbon and nitrogen zooplankton signatures. In pelagic zooplankton, δ 13 C% tended toward less depleted values in summer, likely mirroring phytoplankton isotopic signatures [38,39,50]. During thermal stratification, the high growth rates of phytoplankton cells can lead to the consumption of dissolved atmospheric CO 2 , causing a shift in carbon exploitation sources toward the uptake of the HCO 3 − ion [51][52][53][54].…”
Section: Discussionmentioning
confidence: 93%